Inserção de mulheres: um estudo sobre a presença feminina em escolas de educação profissional no Brasil (Belo Horizonte) e em Portugal (Lisboa) - Cardoso, Vera Lúcia (2016)
This thesis constitutes the deployment of the dissertation in Social Science (Anthropology), presented in 2011 at PUC/SP, on women’s inclusion (ex-students) in technical courses of the former Federal Technical School of Minas Gerais, today CEFET-MG. Thus, in order to expand the range of the discussion on this research, we intended to deepen the studies, offering an approach between Brazil and Portugal, on the inclusion of female teachers in technical areas of secondary level courses in public institutions in both countries. Therefore, we started reintroducing relevant issues to the presence of women, but as teaching professional of technical areas in the institutions. Thus, it was established that the research field would be public schools providing professional education in both countries. In Brazil (Belo Horizonte), we selected CEFET-MG, continuing our Masters degree’s studies and, in Portugal, priority was given to a public educational institution that offers vocational technical education, preferably in Lisbon, which was a reference, including the quality of teaching. Our objective of research was to examine the social, historical, cultural and economic aspects that influence the female condition of teachers, identifying, analyzing and comparing the motivation, the significance of their presence and their implications in educational institutions that offer vocational and technological education. The analysis lies in the forms of insertion and the meaning of permanence of teachers in the schools surveyed, and on how the growth of their careers in education happened, especially the technologic profession. The research was qualitative, with semi-structured interviews, supplemented by a characterization form of the interviewees, as well as analysis of documents provided by the educational institutions. The study showed that, in both countries, the faculty board reveals the institution itself, especially technical training areas as minority and specific references in the institutions. It can be noticed that, despite the similarities and differences highlighted in the narratives of teachers, there are common events that mark and differentiate one from the other; they show nuances of gender inequality, discrimination, prejudice and prestige in the areas of technical training, especially in the stories of pioneer women in Brazil. It is evident the similarity in the rhythm and feminization process in socio-professional hierarchy